Dynamic fracturing by successive coseismic loadings leads to pulverization in active fault zones. Issue 4 (18th April 2016) - Aben, F. M.; Doan, M.‐L.; Mitchell, T. M.; Toussaint, R.; Reuschlé, T.; Fondriest, M.; Gratier, J.‐P.; Renard, F.
Abstract: Previous studies show that pulverized rocks observed along large faults can be created by single high‐strain rate loadings in the laboratory, provided that the strain rate is higher than a certain pulverization threshold. Such loadings are analogous to large seismic events. In reality, pulverized rocks have been subject to numerous seismic events rather than one single event. Therefore, the effect of successive "milder" high‐strain rate loadings on the pulverization threshold is investigated by applying loading conditions below the initial pulverization threshold. Single and successive loading experiments were performed on quartz‐monzonite using a Split Hopkinson Pressure Bar apparatus. Damage‐dependent petrophysical properties and elastic moduli were monitored by applying incremental strains. Furthermore, it is shown that the pulverization threshold can be reduced by successive "milder" dynamic loadings from strain rates of ~180 s −1 to ~90 s −1 . To do so, it is imperative that the rock experiences dynamic fracturing during the successive loadings prior to pulverization. Combined with loading conditions during an earthquake rupture event, the following generalized fault damage zone structure perpendicular to the fault will develop: furthest from the fault plane, there is a stationary outer boundary that bounds a zone of dynamically fractured rocks. Closer to the fault, a pulverization boundary delimits a band of pulverized rock. Consecutive seismic events will cause progressive broadening of the band of pulverized rocks, eventually creating a wider damage zone observed in mature faults. Key Points: Experimental dynamic fracturing can lead to pulverization through multiple high‐strain rate loadings with moderate stress Successive transient loadings decrease the pulverization strain rate threshold Consecutive seismic events cause progressive broadening of the band of pulverized rocks in a fault damage zone